Analysis of abundance and ditribution of parrotfish (Leptoscarus vaigiensis) in seagrass ecosystems in Muris Besar Village, Demta District, Jayapura Regency, Papua - Dirk Y. P. Runtuboi; John Dominggus Kalor; Kalvin Paiki; Robert D Jaban; Ervina Indrayani; Vyona Mantayborbir; Fransina A Izaac (Depik, 2024)
Parrotfish is the speciesLeptoscarus vaigiensis. Leptoscarus vaigiensisis a species of fish found in Muris Besar Village's waters, and it lives in seagrass meadow areas. This study aims to find parrot fish species abundance and distribution (Leptoscarus vaigiensis) in seagrass environments. Benefits from this research are anticipated to include supporting data and information, particularly for the fisheries industry in this water area, and significant information for preserving seagrass ecosystems as a specialized habitat for parrotfish (Leptoscarus vaigiensis). The Water Visual Census (UVC) is used to assess parrot habitat in the waterways. Direct observation at the research site is used to learn about and gather data about the object under study. Counting stationary points, transects, timed swimming at stationary sites, divers remaining in one location and surveying a specified radius for a certain amount of time are the major categories into which UVC methods fall. The research locations are Waipa Beach, Ugape Cape, Augara Beach, Muris Besar Village, Demta District, Jayapura Regency, Papua. The highest abundance value is at station 1, with an abundance value of 1,300 ind/m, while the lowest is at station 2, with an abundance value of 700 ind/m. Leptoscarus vaigiensis has a species distribution with a morality index value between 0.33 and 0.50. The distribution of parrotfish (Leptoscarus vaigiensis) in seagrass ecosystems is categorized as comparable according to the criteria for distribution patterns.Keywords:DistributionParrotfishMuris Besar VillagerAbundanceSeagrass beds